A Novel Approach to Quantifying the Effect of the Density of Sand Cores on Their Gas Permeability - Sundaram, Dinesh; Svidró, József Tamás; Svidró, Judit; Diószegi, Attila (Journal of Casting & Materials Engineering, 2022)
The density of moulding mixtures used in the foundry industry plays a significant role since it influences the strength, porosity, and permeability of moulds and cores. The latter is routinely tested in foundries using different solutions to control the properties of the moulding materials that are used to make moulds and cores. In this paper, the gas permeability of sand samples was measured using a custom-made setup to obtain the gas permeability in standard units instead of the usual permeability numbers (PN) with calibrated units. The aim of the work was to explore the effect of density variations in moulding materials on their gas permeabilities. Permeability in this work is quantified in SI units, square metres [m2]. The setup works based on Darcy’s law and the numbers obtained from the measurements can be used to deduce the gas permeability, k, of a sample. Two furan resin bonded mixtures with the same grain size distribution were hand-rammed with varying compaction forces to obtain a variation in density. Cylindrical samples (50 × 50 mm) were prepared using a silica sand aggregate sourced from a Swedish lake. The results of the measurement provided the difference in gas permeability between the samples that have varying densities. The results of permeability were then extrapolated by modifying the viscosity value of the air passed through the sample. In order to find the effect of apparent density variation on the pore characteristics of the samples, mercury intrusion porosimetry (MIP) was also performed. The results were in line with the gas permeability measurements.